Ecosystem Resilience of a South African Mesic Grassland with Change from Rotational to Continuous Grazing - Nomusa Chonco; Rob Slotow; Zivanai Tsvuura; Sindiso Nkuna (Diversity, 2023)
Grazing practices affect the soil and vegetation of grasslands, which further influence the provision of ecosystem services and the productivity of grasslands. We determined the ecosystem resilience of a mesic grassland under three grazing management systems in the Pakkies area, (30°33′08″ S, 29°25′22″ E), South Africa: cooperative (continuously grazed since 2017), commercial (rotationally grazed for >20 years), and communal (continuously grazed for >20 years) farms. This was carried out by measuring the penetration resistance and infiltration, soil nutrients, forage quality contents for livestock, veld condition, plant species composition and richness, and functional diversity. The soils had a higher penetration resistance in the continuously grazed communal farm, while water infiltration was highest in the continuously grazed cooperative farm. The plant species and functional diversity were greater in the rotationally grazed commercial farm than in the continuously grazed communal and cooperative farms. The continuously grazed cooperative farm had the highest veld condition score (97%), while the rotationally grazed commercial and the continuously grazed communal farms had 82% and 56% veld condition scores, respectively. The forage quality and soil nutrients were generally similar among all farms. The lower plant diversity observed with continuous grazing may indicate that the ecological system was not as resilient concerning this type of grazing. However, for forage quality, soil nutrients and veld condition, continuous grazing was resilient, which indicates that rotational grazing may not be better than continuous grazing for livestock production in this specific region. As long as a minimum level of ecological resilience can be retained, continuous grazing can sustain effective animal production, particularly for small-holder farmers.